Electrophysiological characteristics in children with listening difficulties, with or without auditory processing disorder. - Mattsson, Tone Stokkereit; Lind, Ola; Follestad, Turid; Grøndahl, Kjell; Wilson, Wayne; Nicholas, Jude; Nordgård, Ståle; Andersson, Stein (International Journal of Audiology, 2019)
Objective: To determine if the auditory middle latency responses (AMLR), auditory late latency response (ALLR) and auditory P300 were sensitive to auditory processing disorder (APD) and listening difficulties in children, and further to elucidate mechanisms regarding level of neurobiological problems in the central auditory nervous system. Design: Three-group, repeated measure design. Study sample: Forty-six children aged 8–14 years were divided into three groups: children with reported listening difficulties fulfilling APD diagnostic criteria, children with reported listening difficulties not fulfilling APD diagnostic criteria and normally hearing children. Results: AMLR Na latency and P300 latency and amplitude were sensitive to listening difficulties. No other auditory evoked potential (AEP) measures were sensitive to listening difficulties, and no AEP measures were sensitive to APD only. Moderate correlations were observed between P300 latency and amplitude and the behavioural AP measures of competing words, frequency patterns, duration patterns and dichotic digits. Conclusions: Impaired thalamo-cortical (bottom up) and neurocognitive function (top-down) may contribute to difficulties discriminating speech and non-speech sounds. Cognitive processes involved in conscious recognition, attention and discrimination of the acoustic characteristics of the stimuli could contribute to listening difficulties in general, and to APD in particular.